The Trial of Queen Caroline and the Impeachment of President Clinton: Law As a Weapon for Political Reform - Daniel H. Erskine (Washington University Global Studies Law Review, 2008)
This Article addresses the trial of Queen Caroline in the English House of Lords in 1820, and the impeachment in 1998 and trial in 1999 of President Clinton.
Keywords: Constitutional history; Impeachments; Great Britain -- History; Reforms -- United States; Reforms -- Great Britain; Caroline, Queen, consort of George IV, King of Great Britain, 1768-1821